International surrogacy arrangements– Are they in breach of human rights - Takala, Maiju (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis studies whether international surrogacy arrangements violate the human rights of the people that are involved in the arrangements. This study researches what kind of human right violations do cross-border surrogacy arrangements entail from the point of view of the children, the intended parents and the surrogate mother. I will try to examine which rights they possibly breach and how these rights are violated. A detailed study of the private international law rules of different states has been left out of the study. These regulations have been viewed in the scope that is necessary in order to proceed with the study. This thesis incorporates case study, comparative analysis and juridical analysis in order to research the topic. A legal dogmatic method has been applied in this thesis. The research questions will be examined in the current legal landscape of international law and human rights law with the help of literature, international human right treaties, different domestic laws and domestic soft law instruments, decisions of the European Court of Human Rights and decisions of domestic courts. In order to create a general view of the topic I will research different worldwide approaches to surrogacy. After establishing an overview of the field, I study the possible violations these differences in approaches may cause. The situation will be studied from the perspective of the children that are being born and from the perspective of the adults that are involved. As a concluding thought I will briefly address the theme regarding the lack of international regulation. The study states that there is no univocal answer to the question asking whether international surrogacy arrangements lead to human right violations. In cross-border arrangements especially the children’s rights are in danger. The biggest human right problems are related to the recognition of the children in the receiving countries. Whether international surrogacy arrangements lead to human right violations is dependent on the individual aspects of each arrangement. When it comes to the adults involved in surrogacy arrangements, it is clear that international surrogacy arrangements entail exploitative elements towards the surrogate mothers. Concern about exploitation is bigger when the arrangements are performed in low-income countries. This study furthermore states that prohibiting surrogacy arrangements does not violate the rights of the intending parents.